PUPILS, ICT AND TYPOLOGY OF USERS - POLÁŠEK, Radim (Trends in education, 2008)
The article aims at defining typology of ICT users among primary schools pupils with consideration to their preferences and interests. Outlined are groups of users and their characteristics and from consequent research data analysis is verifying proposed ICT user groups.
Keywords: pupils; ICT; information and communication technologies; classification